DETERRMINAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Furqonti Ranidiah; Geby Dinasti (Universitas Muhammadiyah Bengkulu, 2020)
ABSTRACTÂ This study aims to determine the effect of environmental performance, auditcommittee, profitability, Leverage, and company size to corporate social responsibility (CSR) disclosure in companies listed on the Indonesia Stock Exchange. Corporate Social Responsibility disclosure measured by CSR index based on the Global Reporting Initiative (GRI) G4. The population of this study are manufacturing company listed on IndonesianStock Exchange in 2016-2018. Data collected by documentation method and literature study. Sampling using purposive sampling method, and obtained 18 companies in each period. Sources of data obtained from annual reports of companies listed on Indonesia Stock Exchange in 2016-2018. The analytical method for this study uses multiple regression analysis with SPSS 16.The result of this study showed that environmental performance and company size has positiveeffect to CSR disclosure. Audit committee and profitability has not effect to CSR disclosure, while Leverage has negative effect to CSR disclosure.Keywords: Corporate Sosial Responsibility (CSR) Disclosure, environmental performance, auditcommittee, profitability, Leverage, and company size, Global Reporting Initiative (GRI) G4.